Analisis Gerak Dan Karakter Tari Kain Di Pauah V Kecamatan Pauah Kota Padang - Mila Septiana Putri; Nerosti Nerosti (FBS Universitas Negeri Padang, 2020)
This study aims to analyze the variety of movements and characters of Kain Dance in Pauh V, Pauh district, Padang city. This isa qualitative research using a descriptive analysis method. The object of the research wasKain Dance in Pauh V, Pauh district, Padang city.This research focused on the analysis of movements and characters. The data were collected through observation, interview, and documentation. The data analysis was conducted in the form of description, and the data were validated by using triangulation technique by comparing the observation data to the data from interview and documentation. The results of the study generally show that Kain dance is a traditional art performed in batagak gala event in Pauh V, Pauh district, Padang City. Kain dance is danced by 2 men, who face to face perform eight kinds of movements: salam pembuka, sambah, gantuang sabalah, rantak tigo, malapia, mailak, kalatiak, mangepo. The floor pattern of Kain dance is a straight line pattern, and the dancers always face each other from the beginning to the end of the dance.The dominant movement is the silat movement in the form of a defensive attack with the characteristic of Rantak Tigomotion. The analysis found in the movement of Kain Dance can be seen from the elements of motion: energy, space, and time. The quality of strong motions with the use of powerful movement intensity is carried out at a fast tempo.This dance is accompanied by a large volume of movement depicting the character of a man who is dashing and temperament. The temperament character contained in Kain Dance is expressed in the attack and block movements. The music which accompanies Kain Dance is two mancak drums. Kain dance is performed at the groom's house in front of the aisle at night in a day before the wedding party. The dancers wear black shirt, endong pants, deta for a headband, and sasampiang attached to the dancer's waist.